ENCYCLOPEDIA OF ROMAN IMPERIAL CHRONOLOGY - Harvey, Brian K. Link ([S.l.])
1 online resource
Keywords: This reference work provides detailed lists of the names and titles of Roman emperors from Augustus to Severus Alexander, as well as a chronology of significant historical events and a brief overview of imperial portraiture for each of these emperors. The names, titles, and portraits of the emperor appeared in a wide variety of public contexts, making them some of the most important means of contact between the emperor and his subjects as well as vehicles for the spread of imperial ideology. Being able to precisely date changes in titulature and portraiture is useful not only for the study of imperial ideology but also in providing a chronological context for the inscriptions and statues that bore the emperor's name or face. Along with comprehensive chronological data and tables detailing specific changes in nomenclature and titulature, this volume also discusses selected inscriptions, coins and papyri as examples. The lists also include important historical events during an emperor's reign to give further context and a better understanding of changes in names and titles and a brief overview of the development of imperial portraiture for each emperor. Encyclopedia of Roman Imperial Chronology is an essential reference work for any scholar working on the Roman Empire, in particular epigraphers, numismatists, papyrologists, and archaeologists.